PENGARUH KOMPETENSI APARATUR DESA TERHADAP KUALITAS PELAYANAN PUBLIK DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MEDIASI PADA PEMERINTAH DESA KERTA JAYA - Peni Yusisca; Muhammad Fauzan; Widyawati Widyawati (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
With the use of IT as a moderating variable, this research seeks to ascertain the relationship between the competency of village officials and the quality of public services in Kerta Jaya Village Government. With an explanatory study type, this research takes a quantitative technique. Using a total sampling approach, 36 respondents were selected from the population of all officials engaged in the provision of public services in Kerta Jaya Village. Multiple linear regression analysis was used to examine the data gathered from Likert-scale surveys. The findings indicate that, at least in part, the level of public service quality is unrelated to the level of competence of village officials. This suggests that the study's village authorities' competency has not been able to significantly improve the community's service quality. The quality of public services is positively and significantly impacted by information technology, nevertheless. Thus, it stands to reason that service quality improves in correlation with the degree of information technology adoption. On the other hand, service quality is greatly impacted by both the proficiency of village authorities and the state of information technology. This shows that the use of technology in conjunction with the competency of officials is a key component in enhancing the standard of public services.